Analisis Metode Simple Additive Weighting (Saw) Dan Technique For Order Performance By Similarity To Ideal Solution (Topsis) Dalam Pemberian Insentif Guru di Pesantren Nafidatunnajah - A.Nurul Anwar; Dani (Journal of Research and Publication Innovation, 2024)
Incentives are awards given by an agency or institution to motivate teachers so that their work productivity is high, so that enthusiasm for teaching and loyal attitudes towards Islamic boarding schools will be better. Nafidatunnajah Islamic Boarding School is a private institution operating in the social and educational sector in Rawakalong, Gunung Sindur District. which always strives to continuously improve quality, one of the efforts made is by conducting an assessment of teacher performance at the end of each year using several assessment criteria, namely Morals, Responsibility, Communication, Caring, Discipline, Appearance, Activeness and Language Ability. There are so many methods used to help in this decision making process. However, the research wants to analyze two methods of providing teacher incentives at the Nafidatunnjah Islamic Boarding School, namely the Simple Additive Weighting (SAW) Method and the Technique For Order Performance By Similarity To Ideal Solution (TOPSIS). After making a comparison for each weight of the SAW method and TOPSIS method, it can be concluded that the sum of ranking changes with the largest weight value for each method, alternative 12 is equally selected. With the largest weight range in the SAW method, namely 0.96 and the TOPSIS method of 0.92. so the SAW method is the most relevant method for solving this case.